A universal coating strategy for inhibiting the growth of bacteria on materials surfaces - Zhang, Jie; Wang, Min; Hu, Liwei; Zhang, Qiang; Chen, Enni; Wang, Zhongchao; Shi, Yidong; Tan, Lin; Xiao, Shimeng (Frontiers in Chemistry, 2022)
The development of a versatile antibacterial coating, irrespective of material characteristics, is greatly attractive but still a challenge. In this work, mussel-inspired dopamine-modified sodium alginate (SA-DA) was successfully synthesized as the adhesion layer, and antibacterial coatings on three types of substrates, namely cotton fabric, aluminum sheet, and polyurethane membrane, were constructed through the layer-by-layer (LbL) deposition of polyhexamethylene guanidine and sodium alginate. Among the coated materials, the coated cotton fabric was systematically characterized, and the results showed that it still exhibited ideal hydrophilicity, and its liquid absorption capacity increased with an increase in the coating layers. The growth of Escherichia coli and Staphylococcus aureus was notably inhibited on the coated cotton fabric, and 10 coating bilayers achieved 100% inhibition of bacterial growth within 10 min. Furthermore, an ideal antibacterial ability maintained after 10 cycles of antibacterial trials or 50 washing or soaping cycles. In vitro evaluation of the hemostatic effect indicated that the coated cotton fabric could promote blood clotting by concentrating the components of blood and activating the platelets, and no significant hemolysis and cytotoxicity were observed in the coated cotton fabric. Moreover, the coated aluminum and polyurethane film also displayed an obvious antibacterial effect, which proved that the constructed coating could successfully adhere to the metal and polymer surfaces. Therefore, this work provided a proper way for the progress of a current antibacterial coating tactics for different substrate surfaces.